2012
DOI: 10.1016/j.neuropharm.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of EAE and prevention of blood–brain barrier breakdown after vaccination with novel bifunctional peptide inhibitor

Abstract: The efficacy of bifunctional peptide inhibitor (BPI) in preventing blood-brain barrier (BBB) breakdown during onset of experimental autoimmune encephalomyelitis (EAE) and suppression of the disease was evaluated in mice. The mechanism that defines how BPI prevents the disease was investigated by measuring the in vitro cytokine production of splenocytes. Peptides were injected 5 to 11 days prior to induction of EAE, and the severity of the disease was monitored by a standard clinical scoring protocol and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 44 publications
(56 reference statements)
1
44
0
Order By: Relevance
“…Secondly, lovastatin can inhibit ICAM-1/LFA-1-mediated immune cell adhesion via binding to the I-domain of CD11a of LFA-1 [26]. As shown previously with BPI molecules, the PLP-cIBR molecule could prevent the infiltration of leucocytes by blocking ICAM-1/LFA-1-mediated immune cell adhesion to the vascular endothelial cells of the BBB as well as preventing BBB leakiness [16]. Finally, the underlying mechanisms of in-vivo activity of Ac-PLP-cIBR-NH2-1 and lovastatin were investigated by determining cytokine secretion phenotypes and their effect on pathologies of the brain.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Secondly, lovastatin can inhibit ICAM-1/LFA-1-mediated immune cell adhesion via binding to the I-domain of CD11a of LFA-1 [26]. As shown previously with BPI molecules, the PLP-cIBR molecule could prevent the infiltration of leucocytes by blocking ICAM-1/LFA-1-mediated immune cell adhesion to the vascular endothelial cells of the BBB as well as preventing BBB leakiness [16]. Finally, the underlying mechanisms of in-vivo activity of Ac-PLP-cIBR-NH2-1 and lovastatin were investigated by determining cytokine secretion phenotypes and their effect on pathologies of the brain.…”
Section: Introductionmentioning
confidence: 69%
“…Co-capping experiments showed that I-A g7 and ICAM-1 receptors were co-localized on the surface of GAD-BPI-treated APC, and binding of GAD-BPI on the APC was blocked by either anti-I-A g7 or anti-ICAM-1, suggesting that the BPI molecule can bridge MHC-II and ICAM-1 on the surface of APC [15]. The inhibition of immunological synapse formation alters the differentiation of T cells from inflammatory to regulatory cells [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of antigen specificity to such an approach may reduce undesired side effects associated with global immunosuppression that accompanies many of the current immunomodulatory therapies available (4-7). Indeed, several groups have begun investigating antigen-specific immunotherapies to treat autoimmune disorders (22)(23)(24)(25)(26)(27)(28)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a bifunctional peptide inhibitor (BPI) demonstrated the importance of co-delivering both antigenic peptide and a peptide inhibiting T cell activation by blocking immune cell adhesion (22,23,(26)(27)(28). Applying this codelivery approach of autoantigen and peptide inhibitor to a multivalent delivery vehicle (SAgA PLP:LABL ), i.e., multiple copies of peptide per therapeutic molecule, has also suppressed EAE (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation